Nitrogen use Efficiency of Soil and Foliar Application of 15n Labelled Urea with or Without Inoculation and Micronutrients by Groundnut (Arachis Hypogaea L) in a Semi-Arid Environment (Journal of Science and Technology, 2016)
The N use efficiency by groundnut (Arachis hypogaea L.) grown in the field on a sandy loam soil (Plinthaaualp in Ghana was estimated using 15N labelled urea applied to the soil at planting on one hand and urea in an NPKS nutrient solution sprayed during the pod-filling stage of the crop on the other. The efficiency of the 15N utilization was low and ranged from 26.2 to 17.3% when the urea was applied to the soil, and 14.3 to 24.8% with the foliar spray. The results suggest active absorption of the applied N through the root system of the groundnut at the pod-filling stage. Seed inoculation application of Mo significantly reduced the 1-) N use efficiency.